Sum year we're having

Geometry Level 4

If k = 1 2015 cot 1 ( 2 k 2 ) = cot 1 ( a b ) , \displaystyle\sum_{k=1}^{2015} \cot^{-1}(2k^{2}) = \cot^{-1}\left( \dfrac{a}{b} \right), where a a and b b are positive coprime integers, then find a + b . a + b.


The answer is 4031.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Note that cot 1 ( 2 k 2 ) = cot 1 ( 1 + 1 k ) cot 1 ( 1 + 1 k 1 ) . \cot^{-1}(2k^{2}) = \cot^{-1}(1 + \frac{1}{k}) - \cot^{-1}(1 + \frac{1}{k - 1}).

This follows from the identity cot 1 ( a ) cot 1 ( b ) = cot 1 ( a b + 1 b a ) . \cot^{-1}(a) - \cot^{-1}(b) = \cot^{-1}\left( \dfrac{ab + 1}{b - a} \right).

So we end up with a telescoping series with only

cot 1 ( ) + cot 1 ( 1 + 1 2015 ) = 0 + cot 1 ( 2016 2015 ) -\cot^{-1}(\infty) + \cot^{-1}(1 + \frac{1}{2015}) = 0 + \cot^{-1}(\frac{2016}{2015})

remaining. Thus a + b = 2016 + 2015 = 4031 . a + b = 2016 + 2015 = \boxed{4031}.

Perfect Solution. Did the exact same way.

And just to add another way telescoping that -

cot 1 ( 2 k 2 ) = tan 1 ( 2 4 k 2 ) = tan 1 ( 2 1 + ( 4 k 2 1 ) ) = tan 1 ( ( 2 k + 1 ) ( 2 k 1 ) 1 + ( 2 k + 1 ) ( 2 k 1 ) ) = tan 1 ( 2 k + 1 ) tan 1 ( 2 k 1 ) \cot^{-1}(2k^2) = \tan^{-1}\left(\frac{2}{4k^2}\right) = \tan^{-1}\left(\frac{2}{1+(4k^2-1)}\right) \\ = \tan^{-1}\left(\frac{(2k+1)-(2k-1)}{1+(2k+1)(2k-1)}\right) = \tan^{-1}(2k+1) - \tan^{-1}(2k-1)

Kishlaya Jaiswal - 6 years, 2 months ago

Log in to reply

Nice. So we end up with

tan 1 ( 4031 ) tan 1 ( 1 ) = \tan^{-1}(4031) - \tan^{-1}(1) =

tan 1 ( 4031 1 1 + 4031 ) = tan 1 ( 2015 2016 ) = cot 1 ( 2016 2015 ) . \tan^{-1}\left( \dfrac{4031 - 1}{1 + 4031} \right) = \tan^{-1} \left( \dfrac{2015}{2016} \right) = \cot^{-1} \left( \dfrac{2016}{2015} \right).

I actually prefer your way of telescoping. :)

Brian Charlesworth - 6 years, 2 months ago

Log in to reply

Yea! Thanks.

Kishlaya Jaiswal - 6 years, 2 months ago
Subrata Dutta
Mar 28, 2015

cot^-1 (2k^2) = tan^-1 (1/2k^2)= tan^-1 (2k+1) -tan^-1 (2k-1) therefore the summation becomes , tan^-1 (4031) -tan^-1 (1) =.......

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...